Temporal Dynamics of Napier Grass Stunt Disease as Influenced by Napier Grass Clones and Initial Inoculum - Kawube, Geofrey; Otim, Michael; Talwana, Herbert; Alicai, Titus; Mukwaya, Anthony; Kabirizi, Jolly (Journal of Experimental Agriculture International, 2015)
Napier grass stunt disease (NGSD) is the main biotic factor limiting Napier grass production in the East African region. Its management is, however, hampered by inadequate epidemiological information. This study determined the temporal spread of NGSD in Napier grass fields. A field experiment was setup at National Crops Resources Research Institute, Namulonge in Uganda to determine the influence of initial inoculum and clones on the spread of NSD in the field. The experiment was arranged in a randomized Complete Block Design and replicated 4 times. The initial inoculum levels used were 0%, 10%, 20% and 30% while the clones included KW4, local/wild type and P99, respectively. Napier grass stunt disease incidence data was recorded at 60 days intervals starting 90 days after planting up to 450 days. Napier grass was cut back to a height of 5 cm above ground after each data collection. Gompertz model was found to adequately describe NGSD temporal spread, the basis on which all incidence data was transformed. Results indicate that NGSD symptoms appeared in the field after 150 days after planting. However, NGSD incidence at the time was influenced by initial inoculum levels and type of clone. Plots with higher levels of initial inoculum density reached epidemic levels faster than those without. Disease incidence increased with increase in levels of initial inoculum and time, doubling after every 13.8 to 29.8 days, as such the rate of disease spread is moderate. The disease progression was fastest in clone P99 followed by KW4 and least in local. Final NGSD incidence and Area Under Disease Progress Curve (AUDPC) were linearly related with the NGSD incidence at the time the disease was first detected; indicating that incidence at NSD detection can be used to predict the final disease and AUDPC in the field. Therefore, deployment of measures that reduce initial inoculum is important in control of the disease.
Keywords: AUDPC; clone; doubling; gompert; incidence; rate